Pembaharuan islam di Mesir: Analisis pemikiran Qasim Amin tentang emansipasi dan pendidikan perempuan - Masykur, Danial arba asyakir (Maliki Interdisciplinary Journal, 2026)
Islamic reform movements in Egypt in the late nineteenth century constituted an important response of Muslim intellectuals to social, political, and intellectual changes influenced by Western modernity. One of the prominent figures in this reform movement was Qasim Amin, who is widely known for his ideas on women’s emancipation and education. This study aims to analyze the socio-historical background of Egyptian society during the time of Qasim Amin and to examine his main ideas concerning the position and role of women in society. The research employs a qualitative method with a library research approach by analyzing various literature sources related to Islamic reform and the thought of Qasim Amin. The findings indicate that Qasim Amin’s ideas emerged as a response to the social conditions of Egyptian society, which still restricted women’s roles, particularly in education and public life. Through his influential works such as Tahrir al-Mar’ah and Al-Mar’ah al-Jadidah, Qasim Amin emphasized the importance of women’s education, criticized social practices that limited women’s freedom, and called for a reinterpretation of Islamic teachings related to women’s rights and roles. These ideas generated diverse reactions from society, ranging from strong support to significant criticism. Overall, Qasim Amin’s reformist thought was not solely aimed at improving women’s status, but also at promoting broader social progress through education and social reform.